Towards the use of microphysical variables for the assimilation of cloud‐affected infrared radiances. (12th November 2012) - Martinet, P.; Fourrié, N.; Guidard, V.; Rabier, F.; Montmerle, T.; Brunel, P.
Abstract This article focuses on the simulation and the assimilation of satellite infrared observations in convective‐scale numerical weather prediction (NWP) systems. A radiative transfer model that includes profiles for liquid‐water content, ice‐water content and cloud fraction was used to simulate cloud‐affected radiances as background equivalents. This approach avoids the use of cloud parameters (cloud‐top pressure and effective cloud fraction) deduced from a CO2 slicing algorithm and the modelling of clouds by single‐layer clouds. The advanced radiative transfer model was evaluated using infrared observations measured by the Infrared Atmospheric Sounding Interferometer (IASI). The observation‐screening procedure that was developed to improve the selection of usable cloudy scenes led to a good agreement between observations and background equivalents. For that purpose, a radiance analysis of collocated Advanced Very High Resolution Radiometer (AVHRR) pixels inside each IASI field of view was used. The goal of this preliminary work is to assess the feasibility of adding the cloud variables (liquid and ice‐water contents) to the state vector of the assimilation system. The approach is illustrated with one‐dimensional variational (1D‐Var) retrievals. The physical consistency of the 1D‐Var adjustments is verified with real observations. Then observing‐system simulation experiments (OSSE) are used to validate the 1D‐Var retrievals.